Pengaruh Pendidikan Kewirausahaan dan Lingkungan Keluarga terhadap Minat Berwirausaha Mahasiswa Fakultas Ekonomi Universitas Negeri Padang - Hasan Basri Durin; Marwan Marwan (Jurnal Salingka Nagari, 2022)
The purpose of this research is to find out later whether there will be a positive influence simultaneously or partially from the results of the data processing of the entrepreneurship education variable with the family environment variable on the entrepreneurial interest variable from the students of the Faculty of Economics, Padang State University. The subjects in this study were all students of the Faculty of Economics, Padang State University who had taken entrepreneurship courses. The number of samples used in this study in accordance with the results obtained from the formula amounted to 97 students. The dependent variable in this study is the entrepreneurial interest variable (Y). while the independent variables of this study include the entrepreneurship education variable (X1) and the family environment variable (X2). The method for collecting research data is to use a questionnaire which is then distributed via a Google Form link. The data analysis technique in this research is using descriptive statistical analysis techniques, multiple regression analysis, F test, test, and the coefficient of simultaneous determination (R2). The results of this study indicate that the variables of entrepreneurship education and family environment variables have a positive influence on the entrepreneurial interest variable. This is supported by the results of simultaneous testing (f test), where the significance value obtained in this study is 0.000 (<0.005) simultaneously.